Analisis Hubungan Kualitas Layanan dan Citra Rumah Sakit terhadap Loyalitas Pasien dengan Kepuasan Pasien di Poliklinik Rawat Jalan RSUD Depati Hamzah Pangkalpinang - Asih Purnama Sari; Dedek Sutinbuk; Masagus Hakim; Taufik Kurrohman; Zenderi Zenderi (Universitas Hang Tuah Pekanbaru, 2026)
Patient loyalty is a crucial indicator of hospital service performance, particularly in an era of increasing competition and rising patient expectations for service quality. RSUD Depati Hamzah Pangkalpinang, as a major referral hospital, faces challenges related to service complaints and institutional image, which may influence patient satisfaction and loyalty. This study aimed to analyze the relationships between service quality, hospital image, and patient loyalty, as well as to examine the mediating role of patient satisfaction. This study employed an observational analytic design with a cross-sectional approach. A total of 385 respondents were recruited using quota sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with one-tailed hypothesis testing at a 5% significance level. The results showed that service quality was positively and significantly associated with patient satisfaction (p < 0.05), whereas its direct relationship with patient loyalty was not statistically significant. Hospital image was positively and significantly associated with both patient satisfaction and patient loyalty (p < 0.05). Patient satisfaction was also positively and significantly associated with patient loyalty (p < 0.05). Furthermore, the mediation analysis demonstrated that patient satisfaction significantly mediated the relationships between service quality and patient loyalty, as well as between hospital image and patient loyalty. These findings highlight the important role of patient satisfaction in strengthening patient loyalty. Therefore, improving service quality and enhancing the hospital's institutional image, particularly through strategies that increase patient satisfaction, may contribute to building sustainable patient loyalty.